Mental abilities and performance efficacy under a simulated 480-m helium–oxygen saturation diving - Hou, Gonglin; Zhang, Youlan; Zhao, Na; Chen, Ruiyong; Xiao, Weibing; Yu, Hao; Wang, Jiachun; Yuan, Ti-Fei (Frontiers in Psychology, 2015)
Stress in extreme environment severely disrupts human physiology and mental abilities. The present study investigated the cognition and performance efficacy of four divers during a simulated 480 meters helium-oxygen saturation diving. We analyzed the spatial memory, 2D/3D mental rotation functioning, grip strength, and hand-eye coordination ability in four divers during the 0 – 480 meters compression and decompression processes of the simulated diving. The results showed that except for its mild decrease on grip strength, the high atmosphere pressure condition significantly impaired the hand-eye coordination (especially at 300 meters), the reaction time and correct rate of mental rotation, as well as the spatial memory (especially as 410 meters), showing high individual variability. We conclude that the human cognition and performance efficacy are significantly affected during deep water saturation diving.